Guided Self-Help for Prevention of Depression and Anxiety in Women with Breast Cancer. (24th October 2012) - Komatsu, Hiroko; Hayashi, Naoko; Suzuki, Kumi; Yagasaki, Kaori; Iioka, Yukiko; Neumann, Joyce; Nakamura, Seigo; Ueno, Naoto T.
Abstract : Depression and anxiety are prevalent in women with breast cancer. We developed a self-help kit as a self-learning package of necessary preparatory information (basic knowledge on chemotherapy, side effects, and problem-solving skills). We provided an oncology nurse-guided self-help kit with a cognitive behavioral therapy approach to 46 women with breast cancer in the intervention group and usual care to 36 in the control group in outpatient chemotherapy settings. The oncology nurse monitored and facilitated the patient's progress using the diary during the patient's chemotherapy. We also provided professional-led support group programs. Depression, anxiety, and quality of life were measured at baseline, 1 week, 3 months, and 6 months. The chi-square test and t were used to examine differences between the two groups, and repeated measures analysis of variance was used to test the effects of the intervention on the measures over time. All depression and anxiety scores were improved in both the intervention and control groups, but there were no significant differences between the two groups. Further studies are needed to evaluate the effectiveness of an oncology nurse-guided self-help approach for cancer patients.